Model perawatan untuk penderita penyakit ginjal kronis: Sistematika Review - Julika Siagian, Heriviyatno; Alifariki, La Ode (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Chronic kidney disease (CKD) is a common disease and places an increasing burden on patients and health services. However, the optimal treatment model for patients with CKD remains unclear. We systematically reviewed the clinical effectiveness of different care models for the management of CKD. A comprehensive search of eight data bases was conducted for articles published from 1992 to 2024. We included randomized controlled trials assessing any model of care in the management of adults with pre-dialysis CKD, reporting renal, cardiovascular, mortality and other results. Data extraction and quality assessment were performed independently by two authors. The results are summarized narratively. Nine articles (seven studies) were included. Four models of care were identified: nurse-led, multidisciplinary specialist team, pharmacist-led, and self-management. Nurse-led and pharmacist-led care reported increased rates of prescribing of medications relevant to CKD. High heterogeneity between studies and across studies carries a high risk of bias. Nurse-led care and multidisciplinary specialist care were associated with small improvements in blood pressure control. Evidence of long-term improvements in renal, cardiovascular or mortality endpoints is limited by short follow-up.